The Effectiveness of the Round Table Model Assisted by Word Card Media in Improving Poetry Writing Skills of Tenth-Grade Students at SMAN 1 Cibitung - Bima Maulidan Syah; Roni Nugraha Syafroni; Siti Masitoh (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2026)
Students' poetry-writing skills remain relatively low due to limited vocabulary, difficulty in developing ideas, and learning processes that are still dominated by conventional methods. This study aims to determine the effectiveness of the Round Table model assisted by word card media in improving the poetry-writing skills of tenth-grade students at SMAN 1 Cibitung. This research employed a quantitative approach with a quasi-experimental method and a non-equivalent control group design, involving an experimental class and a control class. The research sample consisted of 37 students from class X.K as the experimental class and 38 students from class X.L as the control class. Data collection was conducted through interviews and tests in the form of a pretest and posttest, which were then analyzed using validity tests, reliability tests, normality tests, homogeneity tests, independent sample t-tests, and N-Gain tests. The results showed that the mean score of the experimental class increased from 57 on the pretest to 77 on the posttest, whereas the control class increased from 53 to 61. The independent sample t-test results yielded a significance value (Sig. 2-tailed) of < 0.001, while the N-Gain test results indicated that the experimental class achieved a score of 51.35% compared to 19.11% for the control class. These results demonstrate that the Round Table model assisted by word card media is effective in improving the poetry-writing skills of tenth-grade students at SMAN 1 Cibitung. This study contributes alternative learning models and media that teachers can utilize to help improve poetry-writing skills, particularly in enhancing students' diction and creativity. Keywords: Word cards, Poetry-writing skills, Round Table